Ultrasound Assisted Catheter Directed Thrombolysis in the Management of a Right Atrial Thrombus: A New Weapon in the Armamentarium? - Mohamed Shokr; Ramanjit Kaur; Kevin Belgrave; Arshad Javed; Mahir Elder; Shaun Cardozo; Luis Afonso; Amir Kaki (Case Reports in Cardiology)
Catheter related thrombosis (CRT) is a commonly encountered entity fraught with substantial risk for mortality secondary to various complications including pulmonary embolism (PE), tricuspid regurgitation, endocarditis, right sided heart failure, and cardiogenic and septic shock. CRT carries a mortality rate of 18% in hemodialysis patients and more than 40% in nonhemodialysis patients. Management strategies include systemic anticoagulation, systemic thrombolysis, surgical evacuation, and percutaneous retrieval with no established guidelines. Ultrasound assisted catheter directed thrombolysis emerges as promising modality with a relatively lower risk of hemorrhage compared to systemic thrombolysis. We report a case of a 75-year-old man with dialysis catheter related thrombosis without PE for which ultrasound assisted catheter directed thrombolysis was used successfully as an alternative therapy.